An innovative ease-off flank modification method based on the dynamic performance for high-speed spiral bevel gear with high-contact-ratio. (August 2021) - Mu, Yanming; He, Xueming; Fang, Zongde
Highlights: Wave flank modification method related tohigh contact ratio. Meshing impactconsideringbase pitch difference. Ease-offflank modificationbased on dynamic performance ofspiral bevel gear. Flank modificationaimingat reducing loaded transmission error and meshing impact. Abstract: To reduce the running vibration of spiral bevel gear, an innovative ease-off flank modification method based on the dynamic performance for spiral bevel gear to minimize loaded transmission error (main vibration excitation of gear transmission in low speed range) and meshing impact (main vibration excitation of gear transmission in high speed range) is proposed. First, an innovative wave flank modification method related to high contact ratio, where the concave transmission error is used to replace the parabola transmission error, is proposed to minimize the loaded transmission error of high-contact-ratio spiral bevel gear. Secondly, meshing impact is calculated by considering the base pitch difference generated from loaded deformation. Finally, based on the advanced ease-off technology and wave flank modification method, an optimization model is established to reduce the loaded transmission error and meshing impact of high-speed spiral bevel gear with high-contact-ratio. The numerical results show that compared with optimized second-order spiral bevel gear transmission, the innovative ease-off flank modification method can further reduce the loaded transmission error and meshing impact of high-speed spiral bevel gear with high-contact-ratio, which greatly improves the dynamic performance of high-speed spiral bevel gear in the entire speed range.